Chitosan-CuO Nanoparticles as Antibacterial Shigella dysenteriae: Synthesis, Characterization, and In Vitro Study - Ahmad Fatoni; Ade Chika Paramita; Budi Untari; Nurlisa Hidayati (Jurnal Kimia Sains dan Aplikasi, 2020)
The synthesis of chitosan- CuO nanoparticles was studied. This research’s aims were biosynthesis CuO nanoparticles, synthesis of chitosan-CuO nanoparticles, and used as an antibacterial agent of Shigella dysenteriae. CuO nanoparticles and chitosan-CuO nanoparticles were characterized by FTIR spectroscopy and X-ray diffraction, respectively. CuO nanoparticle was synthesized by the reaction between leaf extract of sweet star fruit (Averrhoa carambola L.) and copper sulfate pentahydrate. Chitosan-CuO nanoparticles were synthesized by a heating method. The suspension of chitosan-CuO nanoparticles was used as an antibacterial agent with a paper disk method. The result showed that the Cu-O group at CuO nanoparticles was detected at a wavenumber of 503, 619, 767, and 821 cm-1. The crystallite size of the CuO nanoparticles was 4.25 nm. Cu-O group bonded at N-H and O-H groups and detected at 3406 cm-1 from the FTIR spectra of chitosan-CuO nanoparticles. The average inhibition zone of chitosan-CuO nanoparticles at concentration 2.500, 5.000, 7.500, and 10.000 ppm to Shigella dysenteriae were 13.57 ± 1.55; 14.90 ± 1.20; 15.97 ± 0.76 and 17.03 ± 1.80 mm, respectively.